Penerapan Rule Based Dengan Algoritma Viterbi Untuk Deteksi Kesalahan Huruf Kapital Pada Karya Ilmiah - Reza Juanda; Ilman Zuhri Yadi (APTIKOM SUMSEL, 2020)
The use of capital letters is one element of the grammar of the Indonesian Spelling General Guidelines (PUEBI). According to the Large Indonesian Language Dictionary (KBBI), capital letters are letters of a special size and shape (larger than ordinary letters), usually used as the first letter of the first word in a sentence, the first letter of the name itself, and so on. The use of capital letters in a paper is required. However, the ability to use letters of public capital still tends to be not so good. The problem is writing that has not followed the Indonesian Spelling General Guidelines (PUEBI) rules. Settlement steps on how to implement an Indonesian Spelling General Guidelines (PUEBI) rule into the software. Therefore, the author will try to make a software that can automatically detect if there are errors in writing according to the rules of general Indonesian spelling guidelines (PUEBI) on documents, journals, bibliography and scientific works